Gestores públicos e treinamento: um estudo de caso na Universidade Federal de Santa Maria - Grassi, Marcelo Renan (2023)
This study aimed to understand how the preparation of new managers (department heads, unit directors and technical-administrative heads) occurs on the UFSM campuses in Cachoeira do Sul, Frederico Westphalen, Palmeira das Missões, in terms of training, in order to identify the difficulties encountered by them in the exercise of their functions, aiming at contribute with a training proposal. The focus of the work was the context in which these managers are inserted, considering that, given the current demands of society, public managers need to be more prepared to face everyday challenges. The theoretical foundation covers topics such as the evolution of public administration in Brazil, people management in the public sector, training and development concepts, managerial skills, university management challenges and training programs for UFSM managers. This research consists of a case study with a qualitative approach, and was built through semi-structured interviews with 15 civil servants (technical-administrative in education and teachers) in the role of management in three UFSM campuses, in the cities of Cachoeira do Sul-RS, Frederico Westphalen-RS and Palmeira das Missões-RS, carried out in person and by videoconference, whose script was composed of 19 open questions. The analysis of responses was performed using the technique of content analysis. As a result, it is noteworthy that UFSM campus managers, in general, have not received the necessary preparation to assume management functions, and this lack of preparation reflects in a series of difficulties faced by these servers, who end up developing a good part of their skills. their knowledge, skills and attitudes, that is, their skills, in an informal way, through their experiences, through challenges, through the teachings of colleagues, former managers, among others. Among the results obtained, the difficulties reported are: lack of knowledge about the structures and processes of the university, management activities, lack of infrastructure and financial resources, people management, planning and organization, legislation involving the university, systems of information, institutional communication, management of financial resources and organizational climate. In these difficulties, managers usually turn to: more experienced colleagues, deans and pro-rectors, department secretaries, campus directors, former managers and colleagues from other campuses. In addition, it was identified that managers end up developing their managerial skills through day-to-day practices and routines, previous experiences, interpersonal relationships and training and qualification courses. Based on this and other information collected throughout this work, it was possible to build, as a final product, the Training Program for UFSM Managers, aimed at training new and future managers of the institution, whose objective is to provide contents and methodologies that more suited to their demands, such as more practical training that is closer to the reality of the institution.